Are there Differences in the Effectiveness of Quantitative Easing in Japan over Time? - Henrike Michaelis; Sebastian Watzka (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
Using a time-varying parameter vector autoregression (TVP-VAR) with a new sign restriction framework, we study the changing effectiveness of the Bank of Japan's Quantitative Easing policies over time. We analyse the Zero-Interest Rate Policy from 1999 to 2000, the Quantitative Easing Policy from 2001 to 2006, and most recently the `Abenomics' monetary policy easing strategy. Our results indicate that there are important differences concerning the effects of Quantitative Easing over time. We find a stronger and longer lasting positive influence of QE shocks on real GDP and CPI especially since 2013. This might reflect the influence of the `Abenomics' program.
urn:nbn:de:bvb:19-epub-21087-7
Keywords: C30; E44; E52; F41; 330; Bayesian time-varying parameter VAR; monetary policy; quantitative easing; zero lower bound